Cardiac injury on admission linked to worse outcomes in hospitalized COVID-19 patients - Zhou Yiwu; Lv Lin; Yao Rong (Vojnosanitetski Pregled)
Background/Aim. The novel severe acute respiratory syndrome coronavirus 2 (SARS Cov-2) has triggered a pandemic that causes a disease with complex clinical manifestations (coronavirus disease 2019, COVID-19). Soon it became clear that patients who had some comorbidities had a bigger chance of getting the severe form of COVID-19. The aim of the study was to investigate if there was a link between cardiac injury and COVID-19 severity and mortality in patients. Methods. All consecutive patients with laboratory-confirmed COVID-19 were included and followed up until discharge or death from January 30, 2020, to April 5, 2020. Results. A total of 261 COVID-19 patients were included, and 29 (11.1%) had cardiac injury on admission. Patients with cardiac injury were older than those without cardiac injury (72.8 vs 55.8 years old) and more likely to be male (82.8% vs 42.2%). Patients with cardiac injury were also more likely to be smokers (31.0% vs 12.5%), more likely to have chronic cardiovascular disease (24.1% vs 7.8%), chronic pulmonary disease (17.2% vs 3.0%), and chronic kidney disease (10.3% vs 2.2%) compared to patients without cardiac injury. Laboratory findings suggested that patients with cardiac injury were more likely to have leukocyte counts > 10 × 109/L, pronounced lymphopenia, direct bilirubin, myohemoglobin, blood urea nitrogen, C-reactive protein, and pro-B-type natriuretic peptide but lower levels of serum total protein and estimated glomerular filtration rates compared to patients without cardiac injury. Patients with cardiac injury experienced more complications (72.4% vs 47.8%), including acute respiratory distress syndrome (20.7% vs 2.7%), acute kidney injury (10.3 vs 0.4%), severe COVID-19 (58.6% vs 11.6%) and death (55.2% vs 3.9%) compared to patients without cardiac injury. Multivariate analyses showed that cardiac injury was associated with an increased risk of severe COVID-19 [hazard ratio (HR) = 8.71, 95% confidence interval (CI) = 2.37−32.04] and death (HR = 20.84, 95% CI = 1.32−328.22). Conclusion. Cardiac injury on admission was associated with a higher risk of disease progression and death in patients with COVID-19.